2017
DOI: 10.1039/c7cp05921c
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory investigation of negative differential resistance and efficient spin filtering in niobium-doped armchair graphene nanoribbons

Abstract: Using density functional theory calculations in combination with a non-equilibrium Green's function method, we explore the transport properties of a niobium-doped (∼3.57%) armchair graphene nanoribbon of dimer length 7 in a two-terminal device configuration. The band structure of the supercell with niobium atoms showed spin splitting near the Fermi level. The spin-dependent transport properties and spin-resolved band structure of electrodes with applied bias values were calculated to understand the spin filter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This finding means the M1 with the AP configuration can be a dual spin filter or a dual spin diode, which is similar to that in the zigzag edged graphene nanoribbons with a greatly improved performance. [46][47][48] Nevertheless, the T k spectra have wholly reversed with the spin configuration transforming from P to AP-1 configuration. One can see from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This finding means the M1 with the AP configuration can be a dual spin filter or a dual spin diode, which is similar to that in the zigzag edged graphene nanoribbons with a greatly improved performance. [46][47][48] Nevertheless, the T k spectra have wholly reversed with the spin configuration transforming from P to AP-1 configuration. One can see from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In recent decade, with the prosperous development of twodimensional materials such as graphene [11][12][13][14], boron nitride (h-BN) sheet [15,16], black phosphorus (BP) [17,18] and transition metal dichalcogenides (TMDCs) [19][20][21][22], increasing number of half-metallic materials have been explored. In particular, graphene nanoribbons (GNR) can display halfmetallicity via altered edge structures, chemical doping, geometric deformation, structural defects and modulation of external electric and magnetic field [23][24][25][26]. For example, Neeraj et al demonstrated the half-metallicity of fluorine passivated graphene nanoribbons (F-GNR) under the influence of external electric field [27], and experimental methods for their fabrication are currently available [28].…”
Section: Introductionmentioning
confidence: 99%
“…As they are stabilized in the ferromagnetic (FM) configuration, however, the spin-filtering property is expected to emerge . Also the nonmagnetic counterparts of zGNRs, armchair graphene nanoribbons (aGNRs), have been discussed in terms of spin filtering. In this case, magnetism has to be transported into the ribbon by inserting magnetic impurities, vacancies, or topological defects …”
Section: Introductionmentioning
confidence: 99%